2021
DOI: 10.3325/cmj.2021.62.241
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder symptoms and coping with the lockdown among help-seeking veterans before and during the COVID-19 pandemic

Abstract: Aim To compare the severity of posttraumatic stress disorder (PTSD) symptoms and of particular PTSD clusters among help-seeking veterans before and during the COVID-19 lockdown. The second aim was to identify the main coping strategies used.Methods Male war veterans (N = 176) receiving outpatient treatment at the Referral Center for PTSD were assessed at baseline (12-18 months before the pandemic declaration in March 2020) and during the COVID-19 pandemic lockdown (March-June 2020). The Life Events Checklist f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In a nationally representative sample of US military veterans, the prevalence of major depressive disorder and PTSD positive screens remained stable while the prevalence of generalized anxiety disorder positive screens increased [ 10 ] and the rate of suicidal ideation decreased nearly 10 months into the pandemic [ 9 ]. Regarding the mental health among treatment-seeking veterans with pre-existing mental health difficulties, the UK study revealed no significant changes in symptoms of PTSD during the pandemic [ 11 ] and a study conducted in Croatia revealed a decrease in PTSD symptoms during the onset of the pandemic as compared to the measurement a year before [ 12 ]. PTSD symptoms and particularly avoidance symptoms may have reduced because of the restrictive measures that prevented greater extent of exposure to reminders of trauma in everyday life.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a nationally representative sample of US military veterans, the prevalence of major depressive disorder and PTSD positive screens remained stable while the prevalence of generalized anxiety disorder positive screens increased [ 10 ] and the rate of suicidal ideation decreased nearly 10 months into the pandemic [ 9 ]. Regarding the mental health among treatment-seeking veterans with pre-existing mental health difficulties, the UK study revealed no significant changes in symptoms of PTSD during the pandemic [ 11 ] and a study conducted in Croatia revealed a decrease in PTSD symptoms during the onset of the pandemic as compared to the measurement a year before [ 12 ]. PTSD symptoms and particularly avoidance symptoms may have reduced because of the restrictive measures that prevented greater extent of exposure to reminders of trauma in everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD symptoms and particularly avoidance symptoms may have reduced because of the restrictive measures that prevented greater extent of exposure to reminders of trauma in everyday life. Adherence to treatment, regularity of appointments, and stability of treatment as all participants continued to be treated as usual (TAU) may also be viewed as a functional coping strategy that prevented considerable risk of worsening PTSD symptoms [ 12 ]. The results emphasize the importance of treatment engagement of veterans who meet criteria for mental disorder, since approximately 60% of them do not seek help because of concerns about stigma, with many expecting to face prejudice and discrimination [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations